2010
DOI: 10.2478/s11535-010-0100-7
|View full text |Cite
|
Sign up to set email alerts
|

Climacostol inhibits Tetrahymena motility and mitochondrial respiration

Abstract: Climacostol is a resorcinol derivative that is produced by the ciliate Climacostomum virens. Exposure to purified climacostol results in lethal damage to the predatory ciliate Dileptus margaritifer and several other ciliates. To elucidate the mechanism of climacostol toxic action, we have investigated the effects of this compound on the swimming behavior of Tetrahymena thermophila and the respiratory system of isolated rat liver mitochondria. When added to living T. thermophila cells, climacostol markedly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…With regard to the mechanism of action, euplotin C and climacostol have been shown to activate programmed cell death by impairing mitochondrial membrane potential and inducing ROS generation (Cervia et al, 2007;Buonanno et al, 2008;Muto et al, 2011). In the case of blepharismins, it was proposed that the induction of ion-permeable channel formation in cell membranes may play an important role in the defensive function of the toxins against predatory ciliates (Muto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the mechanism of action, euplotin C and climacostol have been shown to activate programmed cell death by impairing mitochondrial membrane potential and inducing ROS generation (Cervia et al, 2007;Buonanno et al, 2008;Muto et al, 2011). In the case of blepharismins, it was proposed that the induction of ion-permeable channel formation in cell membranes may play an important role in the defensive function of the toxins against predatory ciliates (Muto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Serial transfer of the cells was performed twice per week. Before observation, the cells in midlog phase were washed three times with observation solution [10 mM 3-(N-morpholino)propanesulfonic acid/Tris (pH 7.2), 1 mM KCl, 1 mM NaCl, and 1 mM CaCl 2 ] ( 49 ) and equilibrated with observation solution for more than 1 h before observation.…”
Section: Methodsmentioning
confidence: 99%
“…Buonanno and Ortenzi [15] demonstrated that the cytotoxic potency of climacostol on free-living freshwater ciliates can be modulated by the substitution of the double bond in the aliphatic chain of the toxin with a single or a triple one. Muto et al [16,17] found that climacostol specifically inhibits respiratory chain complex I in rat liver mitochondria, inducing a consequent generation of reactive oxygen species (ROS). Finally, Buonanno et al [18] and Fiorini et al [9] observed that climacostol can inhibit the growth of human cancer cell lines in a dose-dependent manner and induce apoptosis by triggering the mitochondrial (intrinsic) pathway.…”
Section: Introductionmentioning
confidence: 99%